The extent of compatibility of accounting education in Saudi universities with the second standard of the international education standards (IES 2) - Aljohani, Raya Mehda; Shehata, Mohammed Abdelshakour (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aims to find out the compatibility of accounting education in Saudi universities with the second standard of international education standards (IES2) issued by the International Accounting Education Standards Board (IAESB). This standard focuses on the technical competencies of a professional accountant at the initial development level. The study population consists of 26 Saudi public universities that offer a Bachelor’s program in accounting. The research is based on a descriptive approach by analyzing the content of learning outcomes in syllabus and course descriptions of courses for the accounting departments in Saudi universities. The learning outcomes of these departments are compared with those required in the IES2, and the level of proficiency required is measured using a table describing the mastery levels for the learning outcomes and the technical competence for the IES2 in order to test the study hypotheses. The results show that accounting education in Saudi universities complies with the IES2 in the courses of accounting and financial reports, management accounting, auditing and assurance, the law of regulations and business, and economics. Moreover, it aligns to some extent with the IES2 in tax courses, information technology, finance and financial management, business management and strategy, governance and risk management, and internal control. However, accounting education in Saudi universities does not comply with the IES2 in the courses of business and regulatory environment.